The Indonesian parliament and democratization - Ziegenhain, Patrick, 1969- (Gale virtual reference library, 2008)
Analyses the Indonesian parliament's contribution towards the process of democratization. Contributes not only to research on the Indonesian democratization process, but also to the comparative research on parliaments in transition processes in general.